Occupational health and safety to chemical agents in nurses at Hospital Cayetano Heredia Lima - Tipán Caicedo, Paola Alexandra (2022)
The study tries to verify if an Occupational Health and Safety Control System controls the potential risk of exposure to dangerous chemical agents in nurses of the Cayetano Heredia Lima General Hospital - 2019, with the participation of nurses and experts, through of a survey to both groups, in order to determine the risk of chemical agents that affect people, with low, moderate and high risk, identifying the concern of the nurses and with a favorable opinion to implement the exposure risk control model to chemical agents.   A study has been carried out and with this information and national and international experiences a proposal was drawn up that establishes the measures, with the opinion of experts who indicated the importance of including it in the Occupational Safety and Health Plan, certifying that the model is favorable, the one that should be implemented and was not carried out due to the effects of the pandemic, the study is viable. It remains in the hands of the readers to be able to analyze it, observe it, determine its value and reach the suggestions and recommendations that of style or need are required.